Eficácia do bochecho de quitosana a 0,4% sobre o biofilme e bactérias orais - Vieira, Liza Barreto (2006)
The purpose of this study was evaluate the effectiveness of the chitosan at 0.4 with high molecular weight and high deacetylation degree mouthrinse over the total decrease of the streptococci, Streptococcus mutans, lactobaci/li and over the perceptible bacterial film and gingival bleeding indices. For that, a total of 68 healthy students between 11 and 13 years old, not allergic to crustacean and not users of antibiotics or antimicrobial agent for the last three months or during the treatment, was selected. From those, thirty two individuaIs used the mouthrinse test, and thirty six, the control one. The participants rinsed 10 mL of the solutions twice a day, one during the moming (which was supervised), and another one during the aftemoon (which was not supervised), for fifteen days. The saliva collect for the microbiological analysis, as well as the perceptible bacterial film and gingival bleeding indices check, were made before the use ofthe mouthrinses (base line), immediately after the last mouthrinse on the day (zero time) and fifteen days after (fifteen time). These data were collected at school and the saliva was carried inside the ice to the laboratory. The samples were diluted, and 0.1 mL ofthe 10 -1 dilution was seeded in Rogosa SL agar, for further analysis of the total of lactobaci/lus~ 0.1 mL of the 10-4 dilution in Mitis Salivarius with bacitracin, for S. mutans analysis; and 0.1 mL of the 10-6 dilution in Mitis Salivarius for the analysis ofthe total of streptococcus. The Rogosa SL agar plates were incubated in aerobic at 37°C for 72 hours and the MSB and the MS were incubated in anaerobic in Gaspak@ jars at 37°C for 48 hours for further count ofColonies Former Units (CFUs). The assay was made in duplicate for each bacterial group analyzed. The number of CFUs transformed in LOGlO was analyzed according to the following tests: ANOV A, t of Paired and Not Paired Student, Friedman, Man-Whitney and square-qui test. On the base line, alI the variables analyzed were similar on both tested groups. On both groups, for the total of streptococcus there was no significant difference along the time and for S. mutans there was a statistic significant increase of the CFUs from the base line to the zero time. For the total of lactobaccilus there was no significant difference on the test group along the time, and on the control there was a significant increase ofthe CFUs ITom the base line to the zero time. For both groups, there was significant decrease ofthe perceptible bacterial film index along the time, and that can be explained by the mechanic effect of the mouthrinse over the bacterial film and by the participation of the students on the research which could have motivated him to a better toothbrushing (Hawthome effect). The gingival bleeding index also showed a decrease along the time, even though it was not significant. Therefore, the conclusion of this study was that the chitosan at 0.4 % mouthrinse was not effective on the CFUs reduction of the three bacterial groups analyzed, as well as on the reduction of the perceptible bacterial film and gingival bleeding indices